Assessment of Nurses’ Knowledge Concerning Peritonitis- Dialysis Association in Baghdad Teaching Hospitals - Al-Mansory, Abdul- Kareem; AL-Ani, Betool (Iraqi National Journal of Nursing Specialties, 2006)
Objectives : The study aims to assessing nurses’ knowledge concerning peritonitis- dialysis association at the peritoneal dialysis units, and to identifying the relationship between some nurses’ knowledge and some of their demographic characteristic. Methodology : A descriptive study was carried out at the peritoneal dialysis units in Baghdad Teaching Hospitals started from November 29th 2004 to August 15th, 2005. A purposive sample of (52) nurses was selected from Baghdad Teaching Hospitals. The data were collected through the use of constructed questionnaire, which comprised of (97) items as an interview questionnaire technique as mean of data collection. The reliability of the instrument was determined through a pilot study and the validity through a panel of experts. The data were analyzed through the application of descriptive statistical analysis that includes frequency and percentage, the application of inferential statistics that include the mean of score and Chi-square test. Results : The findings of the study indicated that the peritoneal dialysis nurses have inadequate knowledge about general information concerning peritonitis- dialysis association was, acceptable, knowledge in diagnosis and treatment and adequate knowledge in prevention of peritonitis- dialysis association. Recommendations: it is recommended that special peritoneal dialysis training program and booklets should be designed and presented to these nurses